Contribution of the Dead Sea Scrolls to Textual Criticism and Understanding of the Canonical Book of Daniel - Nel, M (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
What is the relevance of the scrolls found at Qumran and that is related in one way or another to the Book of Daniel? This question is answered in terms of the eight scrolls found at Qumran rendering the biblical text of the Book of Daniel. The contribution of these scrolls to issues relating to textual criticism of the Masoretic text of the Book of Daniel as well as the different versions is discussed. The question is also answered in terms of the nine scrolls found at Qumran that have, or might have, a relationship to the Book of Daniel. The implications of these manuscripts for the Danielic tradition as well as for understanding the canonical book are discussed.